Nishida Kitarō and Muhammad 'Abduh on God and reason: Towards a theology of place. Issue 2 (3rd April 2022) - Botz-Bornstein, Thorsten
ABSTRACT: I compare the Japanese philosopher Nishida Kitaro (1870–1945) with the Egyptian philosopher and reformer Muhammad 'Abduh (1849–1905). Both philosophies emerged within similar cultural contexts. Both thinkers attempt to think relationships between the individual and the universal through organic models. In parallel, both philosophies produce paradoxical positions regarding the integration of reason and religion. Like 'Abduh, Nishida is interested in the unity of God. How do we have to think the unity of God when every unity is only composed of individuals? 'Abduh avoids Aristotelian substances by claiming that the physical world emerges. Similarly, Nishida thinks that the world emerges as a place ( basho ). Both conceptions contradict Aristotelian logic because both avoid the idea of identity, which is necessary for any abstract logic.